Tumefactive eosinophil‐rich non‐granulomatous small vessel vasculitis in the cerebrum in a patient with idiopathic hypereosinophilic syndrome. Issue 3 (11th April 2022) - Noro, Yoshifumi; Miyata, Hajime; Furuta, Takuya; Sugita, Yasuo; Suzuki, Yuki; Kusumi, Masayoshi; Tanabe, Michiharu; Shomori, Kohei
Abstract : The definite diagnosis of central nervous system vasculitis requires pathological verification by biopsy or surgical resection of the lesion, which may not always be feasible. A 74‐year‐old woman with a history of allergic rhinitis, but not asthma, presented with slowly progressive left hemiparesis. Magnetic resonance imaging of the head revealed a heterogeneously enhancing mass involving the right internal capsule and corona radiata. Histological examination of the resected specimen revealed eosinophil‐rich non‐granulomatous small vessel vasculitis with no neutrophil infiltration or foci of microbial infection. Epstein–Barr virus in situ hybridization was negative, and polymerase chain reaction tests for both T‐cell receptor gamma and immunoglobulin heavy‐chain variable region genes did not show rearrangements, excluding the possibility of lymphoma and lymphoproliferative disorders. Blood hypereosinophilia and elevated erythrocyte sedimentation rate were observed; however, anti‐neutrophil cytoplasmic antibodies were not detected. A biopsy of the erythema in the hips and thighs revealed perivasculitis with eosinophilic infiltration within the dermis. Chest computed tomography revealed multiple small nodules in the lungs. Her symptoms, aside from hemiparesis, disappeared after corticosteroid administration. The clinicopathological features were similar to eosinophilic granulomatosis with polyangiitis but did not meet its current classification criteria and definition. This patient is the first reported case of idiopathic eosinophilic vasculitis or idiopathic hypereosinophilic syndrome‐associated vasculitis affecting the small vessels in the brain. Further clinicopathological studies enrolling similar cases are necessary to establish the disease concept and unravel the underlying pathogenesis.